“Colossal, Complexa, Imprescindível”: Tecnologia de Força Bruta e a Usina Hidrelétrica de Itá/SC - Forcelini, Melody (2017)
This dissertation discusses the role of the projects of great load and of the brute force technology in the alteration of landscapes and in the appropriation of rivers on the part of the state in the Brazil history of contemporary. For that, I analyze the construction of the Hydroelectric power station of Itá, in the state of Santa Catarina, from the preliminary studies for his installation until the present time. The Itá Hydroelectric Plant, that constituted, besides, a national technological pattern for the construction of other similar (the Itá Model) enterprises represents the consolidation of an authoritarian and replete vision of discursive nuances, Especially with regard to the appropriation of the Uruguay River for energy production purposes. The complex relationships between state and the natural world, especially characterized by brute-force technology-based enterprises, that is, large-scale and institutionalized appropriation of natural resources, is one of the most fertile fields of Environmental History and Technology. This field of historical knowledge perceives "environment" in the natural and constructed dimensions of the palpable world. In order to achieve the general objective proposed by the dissertation, I worked with official and technical documents related to the construction of the Itá Hydroelectric Power Plant, considering them in the Brazilian political and technological context and in the socioenvironmental context peculiar to Itá, a municipality that was even flooded and rebuilt In function of the enterprise. The dissertation demonstrates that the impetus to control nature and the Uruguay River as a resource for energy production has crossed diverse political conjunctures, from military dictatorship to democratic governments, with profound socio-environmental consequences for the local population of Itá.